Performance assessment of a hybrid SOFC/MGT cogeneration power plant fed by syngas from a biomass down-draft gasifier. (1st October 2018) - Perna, Alessandra; Minutillo, Mariagiovanna; Jannelli, Elio; Cigolotti, Viviana; Nam, Suk Woo; Yoon, Kyung Joong
Highlights: A CHP hybrid power plant SOFC/MGT fed by syngas from a biomass gasifier is studied. The CHP hybrid BG-SOFC/MGT plant is realized by components commercially available. The performance analysis is carried out by using an integrated numerical model. The model validation is performed by means of experimental data. The impacts of some operating parameters on CHP performance is analyzed and discussed. Abstract: Hybrid systems combine two or more power generating devices and make use of the synergism to generate maximum power and offer very high efficiencies. The aim of this work is to investigate the performance achievable from a small-scale hybrid power plant based on the integration between a micro gas turbine (MGT) and a solid oxide fuel cell (SOFC) fed by the syngas generated by a biomass downdraft gasifier (BG). The thermal energy needed to reach the turbine inlet temperature is supplied by the exhausts coming from a catalytic burner in which the SOFC anode and cathode off-gases are burnt. The hybrid BG-SOFC/MGT plant, based on a simplified configuration and realized considering components commercially available, is designed for optimizing not only the electric power generation, but also the thermal power production, in accordance with the promotion of decentralized CHP plants. The performance assessment has been carried out by means of a numerical model, based on thermodynamic/thermochemical approaches and realized by integrating the models of each plant section, developed by using the Aspen Plus software package. The models validation, performed by using experimental data, demonstrates that the results produced are close to those obtained from each unit, so that the overall integrated model can provide a sufficiently accurate prediction of the expected actual hybrid power plant. The effects of some operating parameters on cogeneration performances, such as the MGT pressure ratio and the S/C (steam to carbon) in the SOFC unit, have been evaluated and analyzed. Results show that the best performances are achieved by assuming the MGT pressure ratio equal to 4.5 and the S/C equal to 0. In this case the electric power is 262 kW (SOFC supplies 180 kW), the thermal power is 405 kW and the electric (AC) and cogeneration efficiencies are 35% and 88%, respectively.